Ambohitantelya yuripopovi gen. nov. et sp. nov., a new apterous Mezirinae from Madagascar (Hemiptera: Heteroptera: Aradidae) with unique metathoracic evaporatoria - Heiss, Ernst; Baňař, Petr (Zootaxa, 2013)
In addition to the ten genera of apterous Mezirinae recorded to date from Madagascar, a new genus Ambohitanlelya gen. nov. with uniquely formed metathoracic evaporatoria is erected for the A. yuripopovi sp. nov., which is described and illustrated.